2020
DOI: 10.3389/fgene.2020.557341
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of FUNDC2 and CMC4 on Chromosome Xq28 Is Sufficient to Cause Hypergonadotropic Hypogonadism in Men

Abstract: Background: Hypergonadotropic hypogonadism (HH) is characterized by low sex steroid levels and secondarily elevated gonadotropin levels with either congenital or acquired etiology. Genetic factors leading to HH have yet to be fully elucidated. Methods: Here, we report on genome and transcriptome data analyses from a male patient with HH and history of growth delay who has an inherited deletion of chromosome Xq28. Expression analyses were done for this patient and his unaffected family members and compared to n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…As shown in the database, there are cases with similar and smaller deletions than the fragment exhibiting developmental delay and ventricular septal defect. Moreover, a previous study showed that a patient who harbored a deletion of chromosome Xq28 exhibited growth delay (19). Ultrasound in this case showed ventricular septal defect and FGR, which was similar to the clinical phenotypes reported in the database and literature.…”
Section: Discussionsupporting
confidence: 87%
“…As shown in the database, there are cases with similar and smaller deletions than the fragment exhibiting developmental delay and ventricular septal defect. Moreover, a previous study showed that a patient who harbored a deletion of chromosome Xq28 exhibited growth delay (19). Ultrasound in this case showed ventricular septal defect and FGR, which was similar to the clinical phenotypes reported in the database and literature.…”
Section: Discussionsupporting
confidence: 87%
“…53 FUNDC2 has been reported to be involved in apoptosis, inflammation, and FSH dysregulation, which is important for regulating Sertoli cell proliferation and spermatogenesis. 54 Current studies have not found that TSPAN6 is closely related to spermatogenesis, but studies have shown that TSPAN6 is a negative regulator of RLR pathway mediated immune signal transduction. 55 Collectively, the function of these genes in spermatogenesis remains to be studied, but they can be used as germ cell marker genes in different stages of spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…AKAP4 regulates signal transduction and metabolic pathways that support sperm motility and capacitation and is highly expressed in RStd 53 . FUNDC2 has been reported to be involved in apoptosis, inflammation, and FSH dysregulation, which is important for regulating Sertoli cell proliferation and spermatogenesis 54 . Current studies have not found that TSPAN6 is closely related to spermatogenesis, but studies have shown that TSPAN6 is a negative regulator of RLR pathway mediated immune signal transduction 55 .…”
Section: Discussionmentioning
confidence: 99%